2013
DOI: 10.1111/jsr.12044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, polysomnographic and genome‐wide association analyses of narcolepsy with cataplexy: a European Narcolepsy Network study

Abstract: SUMMARYThe aim of this study was to describe the clinical and PSG characteristics of narcolepsy with cataplexy and their genetic predisposition by using the retrospective patient database of the European Narcolepsy Network (EU-NN). We have analysed retrospective data of 1099 patients with narcolepsy diagnosed according to International Classification of Sleep Disorders-2. Demographic and clinical characteristics, polysomnography and multiple sleep latency test data, hypocretin-1 levels, and genomewide genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 48 publications
4
135
2
8
Order By: Relevance
“…One adult study also found female gender to be associated with a longer time to diagnosis 91 , while another found idiopathic hypersomnia to be associated with later diagnosis 92 . Children with other sleep disorders (e.g., obstructive sleep apnea) often present 93,94 ; thus, the presence of EDS in this younger population should raise suspicions about a possible diagnosis of primary hypersomnia or narcolepsy.…”
Section: Resultsmentioning
confidence: 98%
“…One adult study also found female gender to be associated with a longer time to diagnosis 91 , while another found idiopathic hypersomnia to be associated with later diagnosis 92 . Children with other sleep disorders (e.g., obstructive sleep apnea) often present 93,94 ; thus, the presence of EDS in this younger population should raise suspicions about a possible diagnosis of primary hypersomnia or narcolepsy.…”
Section: Resultsmentioning
confidence: 98%
“…Zukünftige genomweite Assoziationsstudien (GWAS) könnten auf diese Fragen Antworten geben, wie es für andere Schlafstörungen bereits möglich war (z. B. Narkolepsie [25,26,27] und Restless-Legs-Syndrome [28]). Für die einzelnen genetisch bedingten Parkinson-Syndrome ist bereits für einige Formen auch eine Assoziation mit einem RBD in Segregation mit entsprechenden Mutationen vermutet worden.…”
Section: Andere Genetische Parkinson-syndrome Und Rbdunclassified
“…37 In patients with narcolepsy/cataplexy, mean ESS scores of 17 to 20 have been consistently reported, and these scores are significantly greater than those of healthy controls and patients with other hypersomnias. 6,15,38,39 A systematic literature review found that among 35 studies that evaluated the psychometric properties of the ESS in adults, the study quality ranged from excellent to poor, with the majority rated as fair. 40 Most studies were of patients with obstructive sleep apnea (OSA) and/or insomnia, but several included narcolepsy.…”
Section: Sca Les Fo R Scr Een I Ng a Nd D I Ag Nosi S Epworth Sleepinmentioning
confidence: 99%
“…2,3 The prevalence of narcolepsy with cataplexy (narcolepsy/cataplexy) is estimated to be 0.03% to 0.05% of the general population. [4][5][6] The onset of narcolepsy symptoms most often occurs in adolescence, although approximately one-third of patients experience initial symptoms in adulthood. [7][8][9] The two major symptoms of narcolepsy are EDS, with attacks of irresistible sleep, and cataplexy, defined as "generally brief (< 2 minutes), sudden episodes of loss of bilateral muscle tone (us ually symmetrical) with retained consciousness" 10 often triggered by strong emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation